Cultural interpretation of the sacred route path Cotacachi Cayapas national park - Cevallos Calapi, Raúl Clemente; Ruiz Erazo, Victoria Geovanna; Cruz Góngora, Fabio Elton (Tierra Infinita, 2021)
From the beginning of this study symbolic manifestations unravels the complex thought of the Andean culture, and in this way, we want to give sense and meaning to the Sacred trail “trail” located in cotacachi cayapas national park. The department of environment with the indigen organization of Cotacachi UNORCAC considering the sustainable commitment of ecotourism in the Cotacachi Cayapas national park, aims to recover the hierophanic representation of the Cuicocha Lake, which is also a tourist resource that links conservation and sustainable management. This touristic trail has been articulated in a quadripartite division of the Kichwa cosmovision, It is represented by the Andean Cross and in whose interior the solar and lunar calendar emerges, imperative to celebrate the water rites through the exercise of offerings mainly of corn products. Between the theoretical references, Cevallos, Posso, Naranjo and Bedón (2017), Cevallos (2013; 2006), De Murúa (2001), Cervone (2000), Khaarus Randi (1989), De La Vega (1991), Randi (1989) stand out. ), Rostowrowski (1989), Moya (1981). It had applied a qualitative methodology and applied from theethnographic interpretation and direct participation. In-depth interviews with stakeholders were used. And in sum, the Kichwa communities of Cotacachi and in coordination with the cooperating public organizations: MAE, UNORCAC, Kuychi Kucha Committee and PNCC through the construction of the Andean Cross on the Sacred Route Trail clearly contribute to the development of responsible ecotourism in the brand new National Park.